Landmark Studies Impacting the Medical Management of Benign Prostatic Hyperplasia - Lepor, Herbert (MedReviews, LLC, 2003)
The treatment of benign prostatic hyperplasia (BPH) has changed dramatically over the past 10 years. Phase 3 studies of the safety and effectiveness of α-blockers (eg, terazosin and doxazosin) and 5-α-reductase inhibitors (eg, finasteride) for the treatment of BPH began to appear in the literature in 1992. This article reviews the results of landmark studies of these agents, either separately as monotherapy or as combined therapy, for the treatment of BPH. The relationship between prostate size and lower urinary tract symptoms (LUTS) is discussed. Although prostate volume is not as strongly correlated with these symptoms as was once believed, it has been shown to be an important predictor of risk for developing acute urinary retention. α-Blockers represent an effective treatment for LUTS independent of prostate volume; the clinical benefit of finasteride for LUTS is limited primarily to men with large prostates. Finasteride decreases the risk of progression to acute urinary retention and the requirement for surgical intervention; this benefit is greatest in men with enlarged prostates.